SIGNIFICANCE OF CHETAN BHAGAT’S NOVELS IN SHAPING YOUNG MINDS (International Journal of Food and Nutritional Sciences, 2022)
Indian writing in English has a prominent role in reflecting the culture of India and its people. Chetan Bhagat who is one of the best and prominent writers in India reflects the culture and its importance of Indian families in India. This paper reflects on the narrative style and the impact of postmodern culture on the protagonists of the novels of Chetan Bhagat. Chetan Bhagat has concentrated more on the youth in India and he has named them as “new generation”. This new generation youth’s aim, aspiration, technological impact has been discussed. This paper analyses the ideologically legitimise and sanctify the responsible, selfdetermined, self-managed, and self-governed entrepreneurial persons as both ethically acceptable and practically feasible youth of this country.